In-vitro anti-oxidant activity of leaves of Cicer arietinum - Mhamane, Supriya (Indian Journal of Pharmacy & Drug Studies, 2024)
Background: Cicer arietinum also known as chickpea. Chickpea plant belongs to family Fabaceae. Chickpeas are an essential food plant in India, Africa and Central and South America. This study concludes the Cicer arietinum leave’s anti-oxidant activity. It shows anti-oxidant activity and it is used to reduce oxidative stress. Materials and Methods: This work conceived the anti-oxidant activity of leave’s of Cicer arietinum via DPPH scavenging activity and measuring the absorbance at 517nm. Result: The maximum peak of free radical scavenging activity by using ethanolic and hydro-alcoholic extract is observed at 400μg/ml. By comparing both the extract hydro-alcoholic extract shows maximum percentage inhibition. Conclusion: Thus, the high percentage inhibition of hydro-alcoholic extract which is 51.31% can be more effective as an antioxidant than the ethanolic extract.